Compliance of school lunch portions with recommendations - Lima, João (2013)
Introduction: The evaluation and monitoring of school meals either in qualitative and quantitative terms is important to improve the quality of food service, cost control, as well as promoting health and well-being of children. Objective: To compare lunch portions served and consumed with nutritional recommendations. Methodology: The study was conducted Social Institution of the Private sector, in a Portuguese municipality. 48 children aged from 3 to 10 years old were assessed. Anthropometric, sociodemographic data were collected as well the portions served and consumed, of 10 selected menus at lunch. Results: There were no associations between sex, Body Mass Index classes and the portions consumed or served, or influence of the parents' education in food consumption. No significant differences were found between the average food served and consumed in relation to recommendations and between the average portions served and consumed, to the protein and carbohydrates sources, and vegetables, which determines overfeed and food waste. Conclusions: This study demonstrates the need to calculate individual portions and compliance to recommendations to different age groups as well as the training of employees on platting techniques, pondering the purchase of tools that facilitate compliance with the recommended amounts. At the same time it is suggested the implementation of a nutrition education program to promote vegetables consumption.